Experimental and Numerical Investigation on Strengthening Techniques for Double-Wythe Stone Masonry Walls - Doran, Bilge; Hothot, Yasin Murat; Dinc Sengonul, Burcu; Karslioglu, Metin; Ulukaya, Serhan; Yuzer, Nabi (TURKISH CHAMBER CIVIL ENGINEERS, 2025)
Masonry structures represent the architectural and cultural heritage of great historical importance. They have been used for public and residential buildings for several thousand years. Many well-preserved old masonry structures still exist, proving that this construction can overcome loads and environmental impact. These structures have been exposed to lateral and vertical loads and atmospheric influences throughout their lives. In masonry structures, undesirable damage, cracks, and voids may occur due to environmental factors or various natural disasters, such as earthquakes, which may cause the structure to collapse. Different conventional strengthening techniques are available depending on the purpose required for stone masonry walls. This study aims to evaluate the structural behavior of double-wythe travertine stone masonry walls strengthened by carbon fiber reinforced polymer (CFRP). For this purpose, two masonry stone walls, which are made of saw-cut travertine stones and constructed with English bond, a pattern formed by laying alternate courses of stretchers and headers, were constructed and tested under in-plane monotonic lateral load and constant axial load. Lateral load-displacement relations and failure mechanisms were discussed. In addition, triaxial compression tests of stone, mortar, grout, and stone-mortar composite materials were performed to determine constitutive relationships. Furthermore, three-dimensional (3D) nonlinear finite element analysis (NLFEA) of stone masonry walls using the Drucker-Prager (DP) yield criterion was performed for unstrengthened stone masonry walls and strengthened ones with grout injection and CFRP. The study findings revealed that the proposed numerical modeling approach can accurately predict the experimental lateral load-displacement behavior of both strengthened and unstrengthened specimens subjected to in-plane combined axial loading and shear. Additionally, the model demonstrated its capability to simulate the experimental load-displacement and cracking patterns effectively.
Keywords: Carbon fiber reinforced polymer; double-wythe stone walls; grout injection; historical masonry structures; strengthening; SHEAR BEHAVIOR; BRICK MASONRY; BUILDINGS; GROUTS; EARTHQUAKE; DESIGN; PANELS; Engineering